Аскольд і Олмош - Брайчевський, М.Ю. (Археологія, 1994)
Стаття присвячена проблемі русько-мадярських відносин у ІХ ст. — в часи великої мандрівки мадярських племен з Наддонщини до Трансільванії. Автор стверджує мирний в основному характер тих стосунків, що спричинилися до утворення дружнього союзу київського хагана Аскольда і мадярського ватажка Олмоша. В IX в. состоялась великая миграция венгерских племен, вынужденных под давлением печенежских орд переселиться из Подонья (Леведия) в Нижнее Поднепровье (Ателькузу) и далее — в Трансильванию. В результате первого этапа миграции мадьяры вышли из среды политического влияния Византии и попали в среду влияния Киевской державы. В Поднепровье возник союз киевского хагана Аскольда с венгерским вождем Олмошем (отцом Арпада). Этот союз имел дружественный характер. Он распался после государственного переворота 882 г. в Киеве, в результате которого Аскольд был убит, а мадьяры отошли на запад, в Среднее Подунавье. Great migration of Hungarian tribes took place in the 9th cent. Under the pressure of Pechenegi hordes the tribes were impelled to migrale from the Don river area (Levedia) to the Lower Dnieper area (Alclkuza) and then to Transylvania. As a result of tne first stage of migration Magyars ceased to be under political authority of Bizantine and got into the sphere of interests of the Kiev state. That gave rise to the alliance between Kiev bhagan Askold and Hungarian leader Olmosh (Arpad’s father) in the Dnieper territory. Tnat alliance was not a formal but friendly one. It disintegrated after state coup in Kiev in 882, when Askold was killed and Magyars retreated westwards to the Mid Danube territopy.